2020
DOI: 10.3390/nu12113389
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Single Nucleotide Polymorphisms of ELOVL on Biomarkers of Metabolic Alterations in the Mexican Population

Abstract: The elongation of very long chain fatty acids (ELOVL) is a family of seven enzymes that have specific functions in the synthesis of fatty acids. Some have been shown to be related to insulin secretion (ELOVL2), and in the lipid profile (ELOVL6) and patients with various pathologies. The present work focused on the study of ELOVL polymorphs with clinical markers of non-communicable chronic diseases in the Mexican population. A sample of 1075 participants was obtained, who underwent clinical, biochemical, and nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
(34 reference statements)
1
5
0
Order By: Relevance
“…This method precludes the The mechanism for changes in sebum might be related to the alterations in genes responsible for lipids metabolism, 33 and our results also revealed that the genes related to lipid synthesis and metabolism (e.g., FASN, SCD5, FADS1, FADS2, and ELOVLs) were down-regulated in the non-lesional skin of AD and significantly associated with the skin inflammations and barrier features of AD. These genes have been shown to be intimately involved in TG synthesis, [34][35][36][37] so the downregulation of their expression is consistent with our observation of a significant decrease in TG in the skin of AD patients. Analysis of single-cell RNA-sequence data revealed that these dysregulated genes were mainly de-…”
Section: Discussionsupporting
confidence: 91%
“…This method precludes the The mechanism for changes in sebum might be related to the alterations in genes responsible for lipids metabolism, 33 and our results also revealed that the genes related to lipid synthesis and metabolism (e.g., FASN, SCD5, FADS1, FADS2, and ELOVLs) were down-regulated in the non-lesional skin of AD and significantly associated with the skin inflammations and barrier features of AD. These genes have been shown to be intimately involved in TG synthesis, [34][35][36][37] so the downregulation of their expression is consistent with our observation of a significant decrease in TG in the skin of AD patients. Analysis of single-cell RNA-sequence data revealed that these dysregulated genes were mainly de-…”
Section: Discussionsupporting
confidence: 91%
“…Multiple studies reported that obesity is related to several factors, including elevated energy consumption, a sedentary lifestyle, the consumption of alcoholic beverages, smoking, and several genetic factors [ 5 ]. For example, studies have described the positive or negative effects of single nucleotide polymorphisms (SNPs) on metabolic pathways and health conditions [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Results of studies conducted by Liu et al have suggested that DNA‐methylation may play an intermediary role rather than a causal role in the relationship between the ELOVL2 gene and clinical outcomes 25 . Moreover, three ELOVL2 genetic variants were found to be protective factors against high cholesterol and glucose, insulin resistance and high body fat content 27 . Other SNPs in ELOVL2 gene were associated with risk factors of cardiovascular diseases such as total‐ and LDL‐cholesterol, insulin and BMI 27 .…”
Section: Discussionmentioning
confidence: 99%
“…25 Moreover, three ELOVL2 genetic variants were found to be protective factors against high cholesterol and glucose, insulin resistance and high body fat content. 27 Other SNPs in ELOVL2 gene were associated with risk factors of cardiovascular diseases such as totaland LDL-cholesterol, insulin and BMI. 27 Therefore, hypermethylation of ELOVL2 gene in whole blood does not necessarily mirror a risk factor or a mechanism of disease.…”
Section: Discussionmentioning
confidence: 99%